Temporal changes and between-host variation in the intestinal parasite community of Arctic charr in a subarctic lake - Kuhn, Jesper A.; Knudsen, Rune; Kristoffersen, Roar; Primicerio, Raul; Amundsen, Per-Arne (Hydrobiologia, 2016)
Accepted manuscript version. Published version available in Temporal changes and between-host variation in the intestinal parasite community of Arctic charr in a subarctic lake (2016) 783(1), s.79-91. . The occurrence of trophically transmitted intestinal parasites in Arctic charr was analyzed from data material collected over two decades from Lake Takvatn, northern Norway. The main objectives were to investigate (i) between-year variation in parasite infracommunity composition, (ii) between-host variation in infracommunity composition, and (iii) possible interspecific interaction between parasites. The trematode Crepidostomum spp. and the cestode Eubothrium salvelini were most prevalent and had the highest mean intensities whereas the cestodes Proteocephalus sp. and Cyathocephalus truncatus were uncommon taxa. No clear indication of interspecific parasite interactions was evident. By far the most frequent infracommunity composition was E. salvelini co-existing with only Crepidostomum spp. Despite some indications of individual dietary specialization in Arctic charr, this strong species cooccurrence suggests that the majority of fish had been preying on the very different intermediate hosts of both parasites. Overall, even though some sporadic between-year variation was present, no long-term or cyclical variation in infracommunity composition and mean intensity was revealed, suggesting that the host– parasite system is in a steady state. Minor between-year variation was likely the result of changes in habitat and dietary utilization by Arctic charr, possibly linked to documented changes in the fish community structure of the lake.